More airtime for rural radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Responding to the Viewpoint in Spore 84 on rural radio, Samuel Zelehe of Gambella, Ethiopia, stresses that 'Radio is the cheapest media to establish and to use than other ICTs like TV and the Internet. It is rather suitable as a communication...